Independent and joint associations of nutritional status indicators with mortality risk among chronic hemodialysis patients in the Dialysis Outcomes and Practice Patterns Study (DOPPS). - Lopes, Antonio Alberto da Silva (2010)
Texto completo: acesso restrito. p.224-234